Effect of clotrimazole on cytosolic Ca2+ rise and viability in HA59T human hepatoma cells. (April 2013) - Horng, Chi-Ting; Chiang, Ni-Na; Chen, I-Li; Liang, Wei-Zhe; Chen, I-Shu; Kuo, Daih-Huang; Shieh, Po-Chuen; Jan, Chung-Ren
Abstract Clotrimazole is an antimycotic imidazole derivative that interferes with cellular Ca2+ homeostasis. This study examined the effect of clotrimazole on cytosolic Ca2+ concentrations ([Ca2+]i) and viability in HA59T human hepatoma cells. The Ca2+-sensitive fluorescent dye fura-2 was applied to measure [Ca2+]i. Clotrimazole induced [Ca2+]i rises in a concentration-dependent manner. The response was reduced by removing extracellular Ca2+. Clotrimazole-evoked Ca2+ entry was suppressed by store-operated channel inhibitors (nifedipine, econazole and SK&F96365) and protein kinase C modulators (GF109203X and phorbol, 12-myristate, 13-acetate). In Ca2+-free medium, incubation with the endoplasmic reticulum Ca2+ pump inhibitor 2, 5-di-tert-butylhydroquinone abolished clotrimazole-induced [Ca2+]i rise. Inhibition of phospholipase C with U73122 abolished clotrimazole-induced [Ca2+]i rise. At 10–40 µM, clotrimazole inhibited cell viability, which was not reversed by chelating cytosolic Ca2+. Clotrimazole at 10 and 30 µM also induced apoptosis. Collectively, in HA59T cells, clotrimazole-induced [Ca2+]i rises by evoking phospholipase C-dependent Ca2+ release from the endoplasmic reticulum and Ca2+ entry via store-operated Ca2+ channels. Clotrimazole also caused apoptosis.